TRINARĖ DIALOGO STRUKTŪRA FENOMENOLOGINIU POŽIŪRIU. - Gutauskas, Mintautas (Problems / Problemos, 2009)
The thematization of the phenomenological structure of dialogue is presented in the article. It starts with the critique of dialogue as a binomial relation. Based on Husserl's, Waldenfels' and Mickunas' analyses of intentional consciousness and intersubjectivity, the author shows that there is a third linking member -- subject matter -- in every I-Thou binomial relationship. It is the subject matter which the conceptions of Buber and levinas try to eliminate as a non-dialogical aspect. aim of this critical research is not to proceed to the analysis of dialogue as mutual understanding or rational communication, but to grope those planes of the subject matter which are closest to dialogical relationship. the author elucidates the specific character of percepting Thou in dialogical relationship. The significance of the Other's presence in a dialogue and the constitution of polycentric space are investigated. the structure of addressing is described in the aspect of perception. It is also critically revised whether the problem of the cognition of the Other is significant for dialogue theory. the author is looking for the principles that enable the constitution of common sense. He considers that the main principle for the constitution of common sense is "the connection of fulfilment" (Erfüllungszusammenhang), which is disclosed on the ground of Husserl's notion of filling the empty intentions (Erfüllung der leeren Intentionen). The self-perception in a dialogue is investigated in the aspect of the subject matter. Finally, the conclusion is drawn that the trinomial pattern of dialogue enables us to avoid the extreme reductions of a dialogue to a binomial relationship or rational communication and to present the universal structure of the dialogue in the aspect of a corporeal face-to-face contact and perception.